Analisis Perhitungan Debit Air Tanah pada Sistem Penyaliran Tambang Terbuka di Pit X PT. Bukit Asam Tbk., Kabupaten Muara Enim, Provinsi Sumatera Selatan - Trio Mei Kristin Zendrato; Rusli HAR (Departemen Teknik Pertambangan FT UNP, 2021)
The existence of ground water is very dependent on the amount of rainfall and the amount of water that can seep into the ground. Other influencing factors are lithological conditions (rocks) and local geology. Loose sandy soil conditions or rocks with high permeability will facilitate the infiltration of rainwater into rock formations. On the other hand, rocks with strong and compact cementation have the ability to absorb small amounts of water. The problem of water entering the mine site and flooding the mining site is a very important problem for the company. This is because water entering the mining site can interfere with mining activities and result in production delays for the company in achieving the production targets that have been set, so that if this happens, the company will experience losses both materially and time. From the results of the analysis of the calculation of groundwater discharge with the determination of the value of K (hydraulic conductivity), the total groundwater discharge that enters the pit is 10,049 m3/second, 602,94 m3/minute, 36.176,4 m3/hour or 868.233,6 m3/day.